2020
DOI: 10.1097/aog.0000000000003987
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Universal Testing Experience on a Los Angeles Labor and Delivery Unit

Abstract: Personal or nonessential information may be redacted at the editor's discretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…This could be seen in reports by Sutton et al [10], Vintzileos et al [9], Bianco et al [13] and Dória et al [16] All of them were conducted in areas and timepoints with reported high prevalence of infection [24], and showed higher observed SARS-CoV-2 infection prevalence, ranging between 11 and 19%, with up to 15% of asymptomatic confirmed cases among screened population. On the other side, reports by Naqvi et al [25] and Gagliardi et al [12], reported a low performance of universal screening based either on an overall lower disease burden in their region or due to a referred "steady state" of virus circulation, with less than 1% of asymptomatic confirmed cases. In an intermediate epidemiological situation [24] reports by Khalil et al [11], Miller et al [14] and Ochiai et al [26] presented observed SARS-CoV-2 infection prevalence ranging between 3 and 7%, with up to 6% of asymptomatic confirmed cases among screened population, which are similar to our findings.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 94%
“…This could be seen in reports by Sutton et al [10], Vintzileos et al [9], Bianco et al [13] and Dória et al [16] All of them were conducted in areas and timepoints with reported high prevalence of infection [24], and showed higher observed SARS-CoV-2 infection prevalence, ranging between 11 and 19%, with up to 15% of asymptomatic confirmed cases among screened population. On the other side, reports by Naqvi et al [25] and Gagliardi et al [12], reported a low performance of universal screening based either on an overall lower disease burden in their region or due to a referred "steady state" of virus circulation, with less than 1% of asymptomatic confirmed cases. In an intermediate epidemiological situation [24] reports by Khalil et al [11], Miller et al [14] and Ochiai et al [26] presented observed SARS-CoV-2 infection prevalence ranging between 3 and 7%, with up to 6% of asymptomatic confirmed cases among screened population, which are similar to our findings.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 94%
“…Since the first initiation of implementing universal screening programs by Sutton et al [6] and Vintzileos et al [7], several studies were reported from all over the world [18][19][20]. Following high overall and asymptomatic infection rates from New York studies, results from London were reasonable with a soft decrease from almost one in every five women to one in fourteen [3].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important to prevent potential viral spread to other patients and HCWs and mother-to-child transmission when caring for laboring women, in whom delivery can occur before nucleic acid test results are available. In fact, turn-around time of RT-PCR testing is usually >5 hours in most facilities [8,9] and availability of rapid testing is limited [6].…”
Section: Plos Onementioning
confidence: 99%
“…Second, it investigated the questionnaire's performance in the context of both a targeted and a universal viral screening approach in two consecutive periods of the outbreak. Third, it assessed the universal screening approach over a 6-week time period, which may have allowed to better capture the real trend of infection over time among obstetric patients than much shorter study periods [4,6,8].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation